2014
DOI: 10.1261/rna.042788.113
|View full text |Cite
|
Sign up to set email alerts
|

Translation control of TAK1 mRNA by hnRNP K modulates LPS-induced macrophage activation

Abstract: Macrophage activation by bacterial lipopolysaccharides (LPS) is induced through Toll-like receptor 4 (TLR4). The synthesis and activity of TLR4 downstream signaling molecules modulates the expression of pro-and anti-inflammatory cytokines. To address the impact of post-transcriptional regulation on that process, we performed RIP-Chip analysis. Differential association of mRNAs with heterogeneous nuclear ribonucleoprotein K (hnRNP K), an mRNA-specific translational regulator in differentiating hematopoietic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 61 publications
3
40
0
1
Order By: Relevance
“…Moreover, depletion of AUF1 from a leukemic cell line (THP-1) (42) somewhat increases TAK1 levels and stimulates NF-B-mediated gene transcription. In addition, a recent report demonstrated that depletion of hnRNP K also increases TAK1 levels (43). Because these observations are similar to those obtained with CPEB KO mice and cultured cells lacking CPEB, we hypothesize that there might be a causal link between CPEB, AUF1, hnRNP K, and TAK1-dependent inflammation.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, depletion of AUF1 from a leukemic cell line (THP-1) (42) somewhat increases TAK1 levels and stimulates NF-B-mediated gene transcription. In addition, a recent report demonstrated that depletion of hnRNP K also increases TAK1 levels (43). Because these observations are similar to those obtained with CPEB KO mice and cultured cells lacking CPEB, we hypothesize that there might be a causal link between CPEB, AUF1, hnRNP K, and TAK1-dependent inflammation.…”
Section: Discussionsupporting
confidence: 85%
“…Since primary cells respond earlier to LPS, their induction was reduced to 2 h. 24 Upon LPS stimulation wt-BMDM displayed a strong activation of the kinases p38 and ERK 1/2 after 10 min (Fig. 3A lane 2) that was clearly diminished in TLR4 -/--BMDM (Fig.…”
Section: Analysis Of the Lps Response In Primary Macrophagesmentioning
confidence: 94%
“…24 For deep sequencing, small RNA libraries were generated from isolated total RNA. MiRNAs differentially expressed in response to LPS were identified and classified through integration of the miR-Intess TM platform and miRBase libraries.…”
Section: Identification Of Differentially Expressed Mirnas In Lps-actmentioning
confidence: 99%
“…2C). Regulatory hnRNP-K-mRNA interactions have been demonstrated for the 5′ UTR (Evans et al, 2003) and 3′UTR (Liepelt et al, 2014;Naarmann et al, 2008;Ostareck et al, 1997). Protein class annotation using PANTHER allocated five proteins encoded by the 23 mRNAs to cytoskeletal proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NMHC IIA mRNA 5′UTR, 3′UTR and 3′UTR fragments were PCR amplified from K562 cDNA and cloned into pBSIIKS(+) (Stratagene, La Jolla, CA, USA) and pBSIIKS-Luc-pA-NB (Liepelt et al, 2014) using SpeI (5′UTR) and HindIII (3′UTR), to generate pBSIIKS-NMHC IIA-5′UTR, pBSIIKS-NMHC IIA-3′UTR, pBSIIKS-NMHC IIA-3′F1, pBSIIKS-NMHC IIA-3′F2, pBSIIKS-NMHC IIA-3′F3, pBSIIKS-Luc-NMHC IIA-3′F1-pA and pBSIIKS-Luc-NMHC IIA-3′F3-pA. For pBSIIKS-Luc-NMHC IIA-3′F1 S1_M2)-pA and pBSIIKS-Luc-NMHC IIA-3′F1(S2_M3)-pA, gene fragments (Eurofins Genomics, Table S10) corresponding to NMHC IIA-3′F1 with nucleotide exchanges were amplified and cloned into pBSIIKS-Luc-pA-NB. pBSIIKS-Luc-NMHC IIA-3′F1_ΔS1-pA, pBSIIKSLuc-NMHC IIA-3′F1_ΔS2-pA and pBSIIKS-Luc-NMHC IIA-3′F1_ΔS1, S2-pA were generated by site-directed mutagenesis from pBSIIKS-Luc-NMHC IIA-3′F1-pA.…”
Section: Plasmidsmentioning
confidence: 99%